Enhance Effect of Performance, Motivation and Leadership in the Work Environment - Muhammad Isa Indrawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study examines and finds out more clearly the effect of motivation, leadership, and work environment on employee productivity at PT Cipta Mapan Logistik (Linc Group) Medan Branch. As for the problem that the author raised, namely: whether motivation, leadership, and work environment have a significant simultaneous and partial effect on the work productivity of employees at PT Cipta Mapan Logistik (Linc Group) Medan Branch. The method used in this study is a quantitative method involving 55 respondents. Data collection was carried out using the distribution of questionnaires. The data obtained were analyzed using statistical formulas, using multiple linear regression analysis carried out with the SPSS Version 16 program. The leadership variable has the most significant influence on employee productivity of 0.275. The analysis results using the coefficient of determination show that 75.4% of the variation in employee productivity can be explained by motivation, leadership, and work environment at a 0.5% confidence level. At the same time, the remaining 24.6% is explained by other variables not included in this study. The results of the quantitative analysis show that motivation, leadership, and work environment have a significant effect on employee productivity. Based on the research results, the hypothesis is accepted, which states that there is a substantial influence between motivation, leadership, and work environment on the work productivity of PT. Cipta Mapan Logistik (Linc Group) Medan Branch.